Complementarity of Traffic Flow Intersecting Method with Intersection Capacity Analysis - Lanović, Zdenko (Promet - Traffic&Transportation, 2012)
The paper studies the complementarity of the methods from the field of traffic flow theory: methods of traffic flow intersecting intensity and the method for the at-grade intersection capacity analysis. Apart from checking mutual implications of these methods, the proportionality of mutual influences is assessed. Harmonized application of these methods acts efficiently on the entire traffic network, and not only on the intersections that are usually incorrectly represented as the only network operators. Theoretical considerations are illustrated by a practical example. KEY WORDS: traffic flow theory, theory of organization and direction of traffic flows, intersecting intensity of traffic flows, intersection capacity, optimization